2020
DOI: 10.1155/2020/2658795
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Ginseng in the Treatment of Lung Adenocarcinoma Based on Network Pharmacology

Abstract: Background. Ginseng, a traditional Chinese medicine, was used to prevent and treat many diseases such as diabetes, inflammation, and cancer. In recent years, there are some reports about the treatment of lung adenocarcinoma with ginseng monomer compounds, but there is no systematic study on the related core targets and mechanism of ginseng in the treatment of lung adenocarcinoma up to now. Therefore, this study systematically and comprehensively studied the molecular mechanism of ginseng in the treatment of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…These conclusions are in line with other reports on the antitumor activity of ginseng and purified ginsenosides [ 19 , 23 , 25 , 26 , 36 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These conclusions are in line with other reports on the antitumor activity of ginseng and purified ginsenosides [ 19 , 23 , 25 , 26 , 36 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacological effects of ginseng preparations at various levels of regulation of homeostasis have been studied [ 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]; however, network pharmacology studies [ 26 , 33 , 34 , 35 , 36 , 37 , 38 ] at the transcriptomic level of regulation of cellular homeostasis are limited [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions are in line with other reports on the antitumor activity of Ginseng and purified ginsenosides [19,23,25,26,36,[39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacological effects of ginseng preparations at various levels of regulation of homeostasis have been studied [26,[31][32][33][34][35][36][37][38]; however, network pharmacology studies [26,[33][34][35][36][37][38] at the transcriptomic level of regulation of cellular homeostasis are limited [38].…”
Section: Introductionmentioning
confidence: 99%
“…attention for possible use in the treatment of many diseases, including cancer. Studies have increasingly shown that some TCM remedies, including Chinese herbal medicine extracts, single TCM, and TCM formulations, may have anticancer effects (14)(15)(16). TCM has the features of multi-target, multipathway, and multi-action mechanisms, and its mechanism is difficult to clarify.…”
Section: Pharmacological Authentication Of Pathway Enrichmentmentioning
confidence: 99%